Talking Young Femininities - Pichler, P. author. aut Link
XI, 269 p.
Keywords: Talking Young Femininities explores the spontaneous talk of adolescent British girls from different socio-cultural backgrounds, examining the different discursive identities they negotiate in their talk, including the 'cool' private-school-girl, the 'tough' British Bangladeshi girl, and the 'sheltered' East End girl.